Art in Spain and Portugal from the Romans to the Early Middle Ages : Routes and Myths - Walker, Rose (Book collections on Project MUSE., 2016)
In this colorfully illustrated book, Rose Walker surveys Spanish and Portuguese art and architecture from the time of the Roman conquest to the early twelfth century. For generations, scholarly discussions of such art have been complicated by a focus on maps of the pilgrimage roads and images of the Reconquista. Walker contextualizes these aspects by bringing together an exceptionally diverse range of academic studies, including work previously familiar only to Hispanophone audiences. By breaking down chronological, regional, and disciplinary divides that have limited scholarship on the subject for decades, this book enriches the wider English-language literature on early medieval art.